Predictors of the 10‐year direct costs for treating multiple sclerosis. (29th June 2016) - Moccia, M.; Palladino, R.; Lanzillo, R.; Triassi, M.; Brescia Morra, V.
Abstract : Objectives: Disease‐modifying treatments (DMTs) constitute the largest direct medical cost for multiple sclerosis (MS). This study aims at investigating predictors of the 10‐year economic burden for DMT administration and management. Materials and Methods: This study included 537 newly diagnosed, drug naïve relapsing–remitting MS (RRMS) patients, followed up for 10.1±3.3 years. Costs for DMT administration and management were calculated, and referred to each year of observation (annual costs). Possible predictors of disease evolution were categorized into early predictors (age, gender, disease duration, baseline expanded disability status scale (EDSS), 1‐point EDSS progression within 2 years, and annualized relapse rate ‐ARR‐ within 2 years), and long‐term predictors (reaching of EDSS 4.0, conversion to secondary progressive ‐SP‐, ARR, number of DMTs, follow‐up duration). Association between predictors and study outcome was explored using mixed‐effects log‐linear regression models. Results: A 1‐point higher EDSS at diagnosis was associated with 13.21% increase in the annual costs (95%CI=4.16–23.04%). Each additional year of age at diagnosis was associated with a 0.74% decrease in the annual costs (95%CI=−1.43 to‐0.04%). Female gender was associated with a 12.43% decrease in the annual costs (95%CI=−22.61 to‐0.93%). Converting to SP was associated with a 14.26% decrease in the annual costs (95%CI=−14.26 to‐2.94%). Each additional year of follow‐up was associated with a 3.05% decrease in the annual costs (95%CI=−4.51 to‐1.57%). Conclusions: An estimate of the 10‐year costs associated with DMT administration and management can be calculated by analyzing different factors, and might be of particular interest for planning resources needed for treating people with MS.